Peran manajemen dalam meningkatkan produktivitas perusahaan - Tasliyah, Ummu (Maliki Interdisciplinary Journal, 2025)
Productivity is a key performance measure of a company that shows the ability to use minimal resources to produce optimal output. In order for organizational goals to be achieved effectively and efficiently, management plays an important role in directing, managing, and optimizing the entire work process. The purpose of this study is to determine how management functions contribute to increasing company productivity. This method uses literature research from various national scientific journals. Studies show that strategic planning, effective work organization, encouraging leadership, and systematic control can improve business performance and productivity. Therefore, managerial expertise must be included in the company’s long-term plan.